2006
DOI: 10.1523/jneurosci.2273-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Local Field Potentials and Spiking Activity in Macaque Inferior Temporal Cortex Reveals Diagnosticity-Based Encoding of Complex Objects

Abstract: Neurons in the inferior temporal (IT) cortex respond selectively to complex objects, and maintain their selectivity despite partial occlusion. However, relatively little is known about how the occlusion of different shape parts influences responses in the IT cortex. Here, we determine experimentally which parts of complex objects monkeys are relying on in a discrimination task. We then study the effect of occlusion of parts with different behavioral relevance on neural responses in the IT cortex at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 35 publications
9
53
0
Order By: Relevance
“…In this study, we recorded evoked potentials that presumably reflect synchronized modifications of the polarization of large populations of pyramidal cell dendrites (i.e., postsynaptic potentials). Integration of this information in the cell soma may take a few milliseconds (Nielsen et al, 2006;Monosov et al, 2008). However, the latencies we found, ϳ45 ms for visual stimuli, were remarkably similar to those found in monkeys, despite the fact that latencies are usually delayed in humans compared with monkeys, for example in the medial temporal lobes (Mormann et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we recorded evoked potentials that presumably reflect synchronized modifications of the polarization of large populations of pyramidal cell dendrites (i.e., postsynaptic potentials). Integration of this information in the cell soma may take a few milliseconds (Nielsen et al, 2006;Monosov et al, 2008). However, the latencies we found, ϳ45 ms for visual stimuli, were remarkably similar to those found in monkeys, despite the fact that latencies are usually delayed in humans compared with monkeys, for example in the medial temporal lobes (Mormann et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…When diagnostic information is processed (between 150 and 250 ms), visual categorisation systems have computed the information required for categorisation decision and motor behaviour. This would extend findings that inferior temporal cortex neurons in nonhuman primates are sensitive to diagnostic object properties (Freedman et al, 2003;Logothetis et al, 1995;Nielsen et al, 2006;Sigala and Logothetis, 2002) by providing, with a more integrated neural signal, the state transitions leading to the diagnostic representation.…”
Section: Functional Interpretation Of Information State Transitionssupporting
confidence: 52%
“…On the other hand, the dissociation we found between spike and VEP selectivity in V4 is consistent with several studies showing that sensory properties of LFP and SUA at individual cortical sites are qualitatively different (Kreiman et al, 2006;Nielsen et al, 2006;Asher et al, 2007). Specifically, it has been suggested that stimulus-evoked LFP activity rather reflects the sensory characteristics of the intercortical input to an area that local processing within the region (Khawaja et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…This has been taken as evidence for the hypothesis that stimulus-evoked components of LFPs reflect the local average of the underlying spiking population response. In contrast, other studies have shown that stimulus-evoked LFPs carry different information from that contained in spiking activity (Kreiman et al, 2006;Nielsen et al, 2006;Asher et al, 2007;Monosov et al, 2008). For example, a recent study reported a strong correspondence between sensory characteristics of LFPs within a given area and its presumed feedforward input (Khawaja et al, 2009).…”
Section: Introductionmentioning
confidence: 89%